The Increasing of Science Study Result on Object Material Changes througt The Experimental Method - Muslimatun, Siti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The background of this learning improvement research is the low learning outcomes of science students in grade III of SDN Tunggulsari I, Laweyan District, 2021/2022 school year. Students are lazy in following the lessons, which impacts student learning outcomes less, besides the teacher learning methods are still conventional and less varied. Another reason is student learning activities that are still passive. The purpose of this study is 1) Improving student learning outcomes, in the subject matter of Natural Sciences Changing Objects in class III students at SDN Tunggulsari I Laweyan District 2021/2022 Academic Year, 2) Improving Teacher competence in natural science learning, material Changing Objects to students class III SDN Tunggulsari I Laweyan Subdistrict 2021/2022 Academic Year, 3) Experimental Method can be used to change student learning behavior in natural science students grade III SDN Tunggulsari I Laweyan Subdistrict Academic Year 2021/2022.This research is a Classroom Action Research conducted in class III of SDN Tunggulsari I in the academic year 2021/2022 with the number of students 20. The action stage in learning is planning, implementing, observing and reflecting. From the conclusions above it can be seen that the Experimental Method can improve student learning outcomes. The use of the Experiment method can improve teacher competency in learning. The Experimental Method can improve student learning outcomes in students' cognitive mastery and writing skills. Experimental Method can increase student learning activities.